Transcending The Classroom: University Marketing Clinic as A Training and Socially Responsible Strategy - Quintero, Leidy Cecilia López; Sarchi, Leidy Johanna Bastidas; Naspiran, Angélica Lucía Muñoz (Journal of Posthumanism, 2026)
University training in marketing faces the permanent challenge of articulating theoretical references with intervention in real contexts, in a scenario where the digitalization of markets and the complexity of business environments demand professionals capable of analyzing, deciding and communicating with social responsibility. This article presents the results of a quantitative descriptive study, developed with a sample of 82 students of the Marketing Program of the University of Nariño, from a universe of 367 enrolled in the Pasto and Ipiales campuses, with the purpose of diagnosing their perceptions about theory-practice integration and supporting the design of the University Marketing Clinic "MarketLab UDENAR". Data were collected using an online questionnaire of ten closed items, five of them on the Likert scale and five on the multiple choice scale, and were analyzed with basic descriptive statistics. The findings show a significant gap between the conceptual emphasis of the curriculum and the systematic opportunities for application, as well as an almost unanimous demand for the creation of a permanent institutional space for academic consulting in marketing. Based on these results, a theoretical-pedagogical model based on experiential learning, situated learning, authentic evaluation and university social responsibility is proposed, and the operational functioning of MarketLab UDENAR as a training and socially responsible strategy that articulates teaching, applied research and interaction with the regional environment is proposed.